The TRPV3 channel is a mediator of zinc influx and homeostasis in murine oocytes - Emily M. Lopes; Hiroki Akizawa; Oguz C. Koc; Edgar Soto-Moreno; Neha Gupta; Goli Ardestani; Ahmed Z. Balboula; Ingrid Carvacho; Rafael A. Fissore (Proceedings of the National Academy of Sciences, 2025)
Zinc (Zn 2+ ) homeostasis is essential for gametogenesis and reproduction, and its deficiency causes infertility. Oocytes contain higher Zn 2+ levels than somatic cells, and Zn 2+ concentrations in oocytes are far higher than those of other transition metals and increase even more during maturation in preparation for fertilization. Remarkably, it is unknown what transporter(s) or channel(s) mediate Zn 2+ influx in oocytes and whether they are expressed uniformly throughout folliculogenesis. Here, we showed that the functional expression of a member of the t ransient r eceptor p otential family, vanilloid 3, TRPV3, closely follows the dynamics of intracellular Zn 2+ during oocyte maturation, raising the prospect that these events may be functionally linked. Using microfluorometry, we monitored in oocytes of Trpv3 null females the expected rise in Zn 2+ concentrations during maturation. Surprisingly, Zn 2+ levels did not climb, and the overall FluoZin3 signal in Trpv3 null eggs was lower than in control eggs. Electrophysiological recordings showed a large TRPV3 current induced by the agonist 2-APB in WT eggs supplemented with extracellular Zn 2+ that was absent in Trpv3 null eggs; TRPV3 showed a clear preference for Zn 2+ over Ca 2+ . Trpv3 null eggs displayed features associated with Zn 2+ deficient conditions, such as lower IP 3 R1 function, abnormal cortical granule distribution, and disturbed cytoskeletal organization with distinct actin nucleation disorders. Notably, Trpv3 null eggs demonstrated undisturbed Zn 2+ sparks. Our results suggest that TRPV3 is a pivotal member of the Zn 2+ toolkit, mediating Zn 2+ intake during maturation. They also indicate that distinct transporters or channels mediate Zn 2+ influx throughout folliculogenesis.